The effects of gamma irradiation on dielectric properties of Ag/Gd co-doped hydroxyapatites - Kaygili, Omer; Keser, Serhat; Selcuk, A. Birkan; Bulut, Niyazi; Koytepe, Suleyman; Yahia, I. S.; Ates, Tankut (Springer, 2019)
1.0 at% Ag-containing hydroxyapatites (HAps) doped with the different amounts of Gd (e.g., 0, 0.8, 1.6 and 2.4 at%) were synthesized by a wet chemical method and their dielectric properties were investigated before and after gamma irradiation. The changes in the relative permittivity and alternating current (AC) conductivity values of the as-synthesized samples before and after irradiation were investigated using dielectric measurements. It was found that both Gd content and gamma irradiation dose significantly affect the dielectric properties and AC conductivity. It was concluded that especially due to the thermal stabilities and suitable dielectric properties, the as-synthesized Gd-doped Ag containing HAps could be used for bone healing applications.